PREDIKSI PERINGKAT OBLIGASI DENGAN PERSISTENSI LABA, FREE CASH FLOW, DAN RISIKO LITIGASI - Zurohtun, , (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 8 No 2 (2013), 2013)
ABSTRACT This study investigated the usefulness of accounting information (e.g. earnings persistence, free cash flow, and litigation risk) to predict bond rating. Samples consisted of 32 manufacturing firms listed on Indonesian Stock Exchange over 2005-2007 period and rated by PEFINDO. Binary logistic regression was used to test the hypothesis. The hypothesis in this study was supported, whereas earnings persistence, free cash flow, and litigation risk were useful to predict bond rating. Higher earnings persistence would increase bond rating. Higher free cash flow would increase bond rating. This study could not find evidence that higher litigation risk would decrease bond rating. Keywords: bond rating, earnings persistence, free cash flow, litigation risk